Meningkatkan perkembangan bahasa anak menggunakan model talking stick siswa taman kanak-kanak kelompok A - Rubaiyah Rubaiyah (Persatuan Guru Republik Indonesia Kota Banjarbaru, 2021)
This study aims to describe about improving children's language skills in speaking through the talking stick learning model. The research approach used is qualitative with the type of classroom action research. The research instrument is the researcher himself. Collecting data using interviews, observation and documentation. Data analysis uses data collection, presentation, and verification involving teacher activities, children's activities and cognitive abilities. The results showed that through the talking stick learning model, children's language skills in speaking could improve. This type of research is classroom action research which is carried out in 2 cycles. Each cycle consists of 2 meetings with 4 stages, namely planning, implementing actions, observing and reflecting. This research is located in Harapan Masa Kindergarten, South Banjarmasin District, Banjarmasin City. The data taken are in the form of direct practice and final results. The indicator of success in this study is if in the class 85% or more of the number of students get an average of and the average student activity is 75% or more of the number of students in the good category. Thus, it is concluded that the Talking Stick learning model can be used to improve student learning outcomes in group A. Therefore, it is recommended for further learning to use the Talking Stick learning model so that student learning outcomes increase